2020
DOI: 10.1063/5.0024229
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of broadband complex refractive index of synthetic melanin coatings and their changes after ultraviolet irradiation

Abstract: Melanin, with its high refractive index (RI) and broadband absorption, is an important biomaterial responsible for many of the vibrant structural colors observed in nature and for UV protection. Even though the RI plays an important role in the function of melanin, there is an ambiguity in its reported complex RI and a lack of understanding of whether and how the UV radiation, these materials are likely to experience under normal use, will affect the complex RI. Here, we measured the wavelength-dependent (360-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 55 publications
2
33
1
Order By: Relevance
“…Interestingly, experimentally measured surface temperatures were explained by both parts of the spectrum (visible and near-infrared), while the temperature increase in our models was explained more by differences in the visible spectrum. The absorption spectrum of melanin, which is high in the visible range but low in the near-infrared [27,60], could explain this difference for the models of single barbules. When considering the entire feather surface, however, differences in the near-infrared can be caused by variation in feather microstructure, such as arrangement or density of barbules [61].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, experimentally measured surface temperatures were explained by both parts of the spectrum (visible and near-infrared), while the temperature increase in our models was explained more by differences in the visible spectrum. The absorption spectrum of melanin, which is high in the visible range but low in the near-infrared [27,60], could explain this difference for the models of single barbules. When considering the entire feather surface, however, differences in the near-infrared can be caused by variation in feather microstructure, such as arrangement or density of barbules [61].…”
Section: Discussionmentioning
confidence: 99%
“…The spectral power in the 800–1300 nm range was indeed lower for the light source than for sunlight. However, the average spectral power distribution between 800 and 2000 nm is similar, and the absorption of melanin is not very high between the 800 and 1300 nm region [27] and is, therefore, unlikely to affect the results. But differences in the spectral power distribution may explain why iridescent and unstructured melanin-based plumage did not differ in surface temperature across all body regions despite lower near-infrared reflectance in iridescent feathers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another method of synthesizing melanin, while depositing it on a substrate, is to take the approach of polydopamine deposition [152,153], (noting that polydopamine is a close analogue to melanin), as Kwon et al [154] and Park et al did [141], simply by leaving the substrate in the solution as the material is being synthesized per normal methods. Li et al have extended this method to L-dopa [72], making a "truer" melanin with this methodology.…”
Section: Novel Synthetic Methods For Materials Scientistsmentioning
confidence: 99%
“…Finally, it should be noted that the emission spectra obtained for melanin has a smaller than 0.1% quantum yield, indicating that melanin dissipates >99.9% of the UV-Vis energy as heat [71], which naturally leads to the conclusion that melanin is an excellent photo protectant against optical and UV radiation and as such explains why it is found in the skin. To bolster this conclusion, Li et al recently found that melanin's ability to absorb UV radiation increased after an initial exposure to said radiation [72]. However, it is still not well understood what the coupling, internal conversion mechanism is in how melanin transforms optical energy into heat to such a great extent.…”
Section: Unique Physico-chemical Propertiesmentioning
confidence: 99%